A novel 6-quinoxalinamine-based fluorescent probe for real-time detection of palladium(ii) ions in pure water and bio-imaging. (2nd July 2018) - Che, Chuanliang; Chen, Xiangzhu; Wang, Hongmei; Li, Jia-Qi; Xiao, Yumei; Fu, Bin; Qin, Zhaohai
Abstract : A novel fluorescent probeLK based on a quinoxalinamine derivative exhibited excellent selectivity toward Pd 2+ and could be used for bio-imaging. Abstract : A novel quinoxalinamine-containing fluorescent probe (LK ) was designed and synthesized based on coordination for real-time detection of Pd 2+ .LK was easily obtained in high yield by the Suzuki cross-coupling reaction. The quinoxaline group provides the sensorLK with good water-solubility, which is important for monitoring in biological systems. The probe possessed large Stokes shifts and excellent selectivity for detecting Pd 2+ in the presence of various potential interfering metal ions. The detection limit (22 nM) was far lower than the criterion of the World Health Organization in drinking water. Moreover, LK displayed high sensitivity for identification of Pd 2+ in real water samples. More importantly, the sensorLK succeeded in imaging detection of Pd 2+ in live cells with good membrane permeability and low toxicity.